MiRNA-223-5p inhibits hypoxia-induced apoptosis of BMSCs and promotes repair in Legg-Calvé-Perthes disease by targeting CHAC2 and activating the Wnt/β-catenin signaling pathway. - Jiafei Yang; Tianjiu Zhang; Xingtao Zhu; Zhexi He; Xu Jiang; Song Yu; Huajian Gu (PLoS ONE)
Legg-Calvé-Perthes disease (LCPD) involves femoral head osteonecrosis caused by disrupted blood supply, leading to joint deformity and early osteoarthritis. This study investigates the role of miRNA-223-5p in regulating hypoxia-induced apoptosis and enhancing osteogenesis in bone marrow mesenchymal stem cells (BMSCs). Utilizing a juvenile New Zealand white rabbit model of LCPD established through femoral neck ligation, we transfected BMSCs with miR-223-5p mimics, inhibitors, and controls, followed by hypoxic exposure. The impact of miR-223-5p on BMSC apoptosis was assessed using qPCR, Western blotting, and dual-luciferase reporter assays, focusing on the Wnt/β-catenin signaling pathway. In vivo, we evaluated the effects of transplanting miR-223-5p-overexpressing BMSCs into the LCPD model. Our results indicate that miR-223-5p is downregulated under hypoxic conditions. Overexpression of miR-223-5p in BMSCs inhibited hypoxia-induced apoptosis and activated the Wnt/β-catenin pathway by directly targeting CHAC2. In vivo, miR-223-5p-overexpressing BMSCs enhanced femoral head osteogenesis and reduced necrosis in the LCPD model. These findings suggest that miR-223-5p inhibits hypoxia-induced apoptosis in BMSCs by targeting CHAC2 and activating the Wnt/β-catenin pathway, proposing miR-223-5p as a promising target for improving bone repair in ischemic conditions.